Contributions of photochemistry to bio-based antibacterial polymer materials. Issue 47 (22nd November 2021) - Versace, Davy-Louis; Breloy, Louise; Palierse, Estelle; Coradin, Thibaud
Abstract : Contribution of photochemistry for the synthesis of bio-based antibacterial polymer materials. Abstract : Surgical site infections constitute a major health concern that may be addressed by conferring antibacterial properties to surgical tools and medical devices via functional coatings. Bio-sourced polymers are particularly well-suited to prepare such coatings as they are usually safe and can exhibit intrinsic antibacterial properties or serve as hosts for bactericidal agents. The goal of this Review is to highlight the unique contribution of photochemistry as a green and mild methodology for the development of such bio-based antibacterial materials. Photo-generation and photo-activation of bactericidal materials are illustrated. Recent efforts and current challenges to optimize the sustainability of the process, improve the safety of the materials and extend these strategies to 3D biomaterials are also emphasized.